Estudo da typha angustifolia l. como material vegetal adsorvente para a remoção dos agrotóxicos trifluralina, clorpirifós e α-endossulfam de meio aquoso - (:unkn) unknown (Universidade Federal de Goiás, 2016)
Because of the toxicological relevance of pesticides introduced into the environment through agricultural practices, it is necessary to develop simple methodologies with low cost, enabling remove these pollutants from the environment, in particular of water intended for human consumption. The adsorption process is an efficient and low cost technique that have wide application. The adsorbent capacity of the leaves of Typha angustifolia L. herbaceous perennial plant belonging to the family Typhaceae, in Brazil it is also popularly known as taboa, was investigated for the removal of pesticides trifluralin, chlorpyrifos and α-endosulfan from aqueous medium. The the analytical method using solid phase extraction (SPE) and chromatography with electron capture detector (GC/ECD) was optimizates and validate. The validation criterions were reached and the analytical methos was considered efficient for trifluralin, chlorpyrifos and α-endosulfan quantification in an aqueous medium, providing credibility to the results obtained in the adsorption experiments. The adsorption capacity of T. angustifolia was evaluated under different parameters: treatment of the material, amount of material, contact time between the plant material and the pesticides solution and concentration of the pesticides solution. The results showed that treatment of the material with distilled water and was satisfactory and, for all doses evaluated the pesticide removal was efficient, with best results obtained at a dose of 3.0 g L-1 , equivalent to 60 mg of adsorbent in 20.0 mL of solution, in which the pesticide removal were between 73 and 80%. The adsorption kinetics of the pesticide by T. angustifolia showed that the adsorption equilibrium was reached in 40 minutes for all pesticides, removing up to 90% and using a very small amount of plant material (3 g L-1 ). The experimental data were evaluated using the kinetic models of pseudo-first order, pseudo-second order and Avrami. One of the limitations encountered in the concentration influence study is the limited solubility of the agrochemical in aqueous medium (between 0.33 and 1.00 mg L-1 ), resulting in the study of a small concentration range in the adsorption experiments. To study the pesticides adsorption mechanism by T. angustifolia material, the experimental data were applied to Langmuir, Freundlich and Sips non-linear isotherms models. Additional tests showed that the adsorption capacity is unaffected when using natural water in the adsorption experiments. The results indicate that the material obtained from of T. angustifolia leaves, has a great potential to be used as an alternative adsorbent material in pesticide contaminated aqueous solution treatment.
A study of the typha angustifolia l. as plant material adsorbent for removal of pesticides trifluralin, chlorpyriphos and α-endosulfan in aqueous medium
Keywords: Typha angustifolia L.; Trifluralina; Clorpirifós; α- endossulfam; Adsorvente alternativo; SPE; GC/ECD; Typha angustifolia L.; Trifluralin; Chlorpyrifos and α- endosulfan; Alternative adsorbent; SPE; GC/ECD; CIENCIAS EXATAS E DA TERRA::QUIMICA